The Investment Urgency In Ultra Micro Organizational Going Concern - Rohma, Frida Fanani; Syahputra, Bagus Erlangga (Journal of Multidisciplinary Science, 2022)
This study aims to explore and examine the role of investment in encouraging the sustainability of micro-enterprises. This research was conducted using a qualitative method in one of the ultra micro businesses engaged in manufacturing in the food and beverage industry. The results showed that the "Chocolate" Micro business before implementing investment activities experienced profit instability which tended to decrease during 2018-2020, so investment activities must maintain a consistent level of income that may occur due to inflation. Micro business "Chocolate" before investing needs to pay attention to the risk and rate of return of investment value, one of which is using the present time value method.